Implementasi Digitalisasi Administrasi Pendidikan di SMP Negeri 3 Bangli - Suyadnya, I Dewa Putu (Jayapangus Press, 2024)
The implementation of technology in educational administration is a crucial step. Educational administration can experience increased efficiency through the application of technology. By using technology, administrative processes can be carried out more effectively and efficiently. Considering the importance of the role of technology or digitization in daily life, it is essential to conduct research related to the implementation of digitalization in educational administration within the educational institution. This research is a qualitative study aimed at understanding the implementation of digitalization in education at SMP Negeri 3 Bangli. Additionally, the research aims to identify the platforms used in the implementation of educational administration at SMP Negeri 3 Bangli. The data collection methods used in this research are literature review, observation, and interviews. The results of this research indicate that the digitalization implementation at SMP Negeri 3 Bangli is evident in (1) school head programs, (2) the learning process, (3) assessment implementation, (4) data management, (5) school innovation programs, and (6) school publications. The platforms used to support school digitization include Google Classroom, Kahoot, Quizziz, and Melajah.id for digitalizing learning, Google Form and CBT for digitalizing assessment implementation, Google Drive for digitalizing management and data, Google Form and QR Code for innovation programs, and social media platforms such as Facebook, Instagram, YouTube, and the school website for school publications. Additionally, PMM is used for digital teacher training. With this digitalization process, educational administration activities at SMP Negeri 3 Bangli can be conducted more effectively and efficiently.